Components of an effective HR strategy in corporations - Babуch, Anna (Global Prosperity, 2023)
Abstract. The article examines the main elements of a successful HR strategy in large corporations and shows why they are important for long-term development. The central idea is that human resource management should not be reduced to paperwork or routine processes. Instead, it should connect people with the company’s vision and give employees clear conditions to grow and contribute.The text begins with the role of setting clear and realistic goals. Without them, HR activities turn into scattered actions that do not move the company forward. Another key element is corporate culture. It is explained not as posters or slogans but as the real everyday behavior, values, and relationships inside the team. Understanding this culture is necessary in order to build policies that work in practice, not only on paper.The article also highlights the importance of workforce planning. Careful forecasting of staff numbers and qualifications helps prevent shortages or wasted resources. Recruitment and talent acquisition are described as more than filling vacancies: they are about choosing people who fit the company both professionally and personally.Further attention is given to employee development, training, and mentoring. These processes are seen as long-term investments that increase skills and motivation. Motivation and reward systems are presented as tools for building fairness and trust, while performance management ensures regular feedback and improvement.Finally, the article stresses flexibility and innovation as vital features of any HR strategy today. Companies that adapt quickly and support new ideas are better prepared for challenges and stay competitive.